Disabilitas dan Pendidikan: Aksesibilitas Pendidikan Bagi Anak Difabel Korban Kekerasan - Siti Kasiyati; Abdullah Tri Wahyudi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Accessibility of education for people with disabilities has been guaranteed by Law no. 18 of 2016 concerning Persons with Disabilities. However, there is still a lot of data that shows that many children with disabilities do not have access to education, especially children with disabilities who are victims of violence, where in addition to having obstacles to their disabling condition, they also experience deep trauma but the trauma is not immediately known. This study will describe the barriers that occur for children with disabilities in getting access to education widely and what efforts can be made to fulfill the accessibility of education for them. This research methodology uses a qualitative and descriptive-analytical approach by taking the research location at the Aisyiyah Regional Leadership Council of Law and Human Rights, Central Java, which mainly assists children with disabilities who are victims of violence. In this study, it was found that there were obstacles experienced by children with disabilities in getting access to education, from the various obstacles that can be grouped into, barriers that come from parents, the community, government officials, educational institutions, and the children with disabilities themselves. and the efforts made to fulfill the accessibility of education for children with disabilities, namely consultation, investigation, profile assessment, physical healing, psychological healing, advocacy, home visits, psychological counseling, spiritual strengthening, and providing assistance. Aksesibilitas pendidikan bagi difabel telah dijamin oleh UU No. 18 Tahun 2016 tentang Penyandang Disabilitas. Namun, masih banyak data yang menunjukkan banyak anak difabel tidak mendapatkan akses pendidikan apalagi anak difabel korban kekerasan, dimana selain mereka memiliki hambatan terhadap kondisi difabelnya itu sendiri juga mengalami traumatik yang mendalam tetapi tidak serta merta diketahui traumanya. Penelitian ini akan memaparkan hambatan-hambatan yang terjadi bagi anak difabel dalam mendapatkan aksesibilitas pendidikan secara luas dan upaya apa yang dapat dilakukan untuk pemenuhan asksesibilitas pendidikan bagi mereka. Metodologi penelitian ini menggunakan pendekatan kualitatif dan bersifat deskriptif analitis dengan mengambil lokasi penelitian di Majelis Hukum dan HAM Pimpinan Wilayah ‘Aisyiyah Jawa Tengah yang banyak melakukan pendampingan terhadap anak difabel korban kekerasan. Dalam penelitian ini ditemukan adanya hambatan yang dialami anak difabel dalam mendapatkan akses pendidikan, dari berbagai hambatan tersebut dapat dikelompokkan menjadi, hambatan yang berasal dari orang tua, masyarakat, aparat pemerintah, lembaga pendidikan, dan dari diri anak difabel sendiri. dan upaya yang dilakukan untuk pemenuhan aksesibilitas pendidikan bagi anak difabel , yaitu konsultasi, investigasi, profile assesment, penyembuhan fisik, penyembuhan psikis, advokasi, home visit, konseling psikologi, penguatan spiritual, pemberian bantuan.